The bioactivity of bacterium and fungi living associate with the sponge Reniera sp. against multidrug-resistant Staphylococcus aureus and Escherichia coli - AGUS TRIANTO; Nirwani Nirwani; Oktora Susanti; Diansari Siti Maesaroh; Ocky Karna Radjasa (Society for Indonesian Biodiversity, 2019)
Abstract. Trianto A, Nirwani, Susanti O, Maesaroh D, Radjasa OK. 2019. The bioactivity of bacterium and fungi living associate with the sponge Reniera sp. against multidrug-resistant Staphylococcus aureus and Escherichia coli. Biodiversitas 20: 2302-2307. The study aimed to isolate and identify the sponge-associated microorganisms producing the antibacterial substances. The sponge Reniera sp. was collected by hand during skin diving in Karimunjawa Islands, Indonesia. The microbial symbionts were isolated with the dilution method and screened with the overlay method against the MDR S. aureus and E. coli. The bacterium was cultured in Zobell medium, while the fungi were cultured in malt extract broth (MEB) medium. The isolates were identified based on the molecular method. A total of 46 bacteria and 43 fungi were isolated, which 7 bacteria and 20 fungi exhibited antibacterial activity against the MDR E. coli and S. aureus strains. The molecular identification revealed that the active isolates close to Pseudoalteromonas maricaloris (99%), Aspergillus nomius (96%), Eurotium rubrum (99%), and Penicillium sp. (100%). Fractionation of K.J.16.U extract gave a fraction that active to the S. aureus and E. coli strains at concentration 150 and 15 µg disk-1. The fraction K.J.16.U.1.4.4 exhibited stronger activity than that exhibited by chloramphenicol at 150 µg disk-1. The sponge Reniera sp. collected from Karimunjawa Islands comprise bacterial and fungal isolates produced antibacterial compounds that inhibited the growth the MDR E. coli and S. aureus strains.